THE TEACHING STYLE DURING THE PHYSICAL EDUCATION AND SPORT - Finichiu Marin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article is a finding on the style of teaching in physical education, consisting of a set of constants associated with individual behavior and which are located in the region of contact with psycho-pedagogical field and directly perceptible without internal interposition. Forming the style of teaching has as a starting base the behavior of a man, a man characterized by certain personality traits that can be resized, restored, rebalanced. A style represents the fundamental necessities of a "leader" (for example) that motivate behavior change by changing the external circumstances, while the style remains constant.